FUNGSI PENILAIAN OTENTIK (AUTHENTIC ASSESSMENT) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - ANJANI PUTRI.B.P (STAI Sangatta Kutai Timur, 2019)
Authentic assessment is the activity of evaluating students who emphasize what should be assessed, both the process and the results with various assessment instruments. Authentic assessment is also a designation used to describe the real tasks that students need to carry out in producing knowledge to reproduce information. For example, in learning to read a student has not been said to learn meaningfully if he has not been able to make predictions, prove predictions, and retell the contents of the reading. Therefore in learning it is very necessary to do an authentic assessment to ensure the formation of real competencies in students. Some things that become the principle in assessment are that the assessment process must be an inseparable part of the learning process, not a separate part of the learning process (part of, not a part form instruction). Assessment must reflect real world problems, not school world (school work-kind problems). Assessments must use a variety of measures, methods, and criteria that are appropriate to the characteristics and essence of the learning experience. Assessment must be holistic which includes all aspects of the learning objectives (cognitive, affective, and sensory-motor).